The effect of catalyst preparation on the catalytic activity of Ni/MgO-ZrO2 for methane dry reforming - Shieh, Louie C. (Animo Repository, 2010)
Methane dry reforming is a process by which carbon dioxide and methane are converted into syngas, carbon monoxide and hydrogen. Nickel-based catalysts are found to be suitable and cheap catalysts for this process. However, nickel-based catalysts are prone to carbon deposition, which leads to catalyst deactivation. One way to inhibit carbon deposition on the catalyst is by the method of catalyst preparation. This study investigated on the effect of catalyst preparation on the surface characteristics and catalytic activity of Ni/MgO-ZrO2 catalyst prepared by the co-precipitation (CP) and Pechini sol-gel (PCH) preparation methods for methane dry reforming. The catalysts were characterized using the BET, SEM-EDX and TEM, XRD, and AAS, to measure the surface area, pore size, and pore volume, the surface morphology and surface elemental composition, the crystal structure, and total nickel content of the prepared catalysts, respectively. BET results revealed that the surface area, pore volume, and pore size were very similar for both catalysts. EDX results showed that the surface nickel content of the CP catalyst was 51.15% by mass while the PCH catalyst was 23.75% by mass. However, the AAS results revealed a close concentration of nickel for the two catalysts. TEM images revealed that some of the nickel particles were encapsulated by the support of the PCH catalyst due to the simultaneous synthesis of nickel, magnesia, and zirconia in the sol-gel method of preparation. The XRD patterns of both catalysts revealed the presence of a NiO-MgO solid solution, as well as a large difference in the crystalline phase of ZrO2 between the two catalysts. The PCH catalyst was found to have 37.35% tetragonal ZrO2 while the CP catalyst was found to have 88.12% tetragonal ZrO2, the remaining being m-ZrO2. This is due to the oxidation of the carbon species of the polymeric gel of the PCH catalyst during calcination, which caused an increase in the rate of crystallization.